Islamic Social Reporting, Islamic Corporate Governance, Zakat Perfoming Ratio on the Reputation of Islamic Commercial Banks in Indonesia - Muhibuddin; Umiyati; Riza Eko Suswanto; Dwi Irianti Haningdiyah (Akuntansi: Jurnal Akuntansi Integratif, 2023)
Islamic banking always strives to improve its reputation in the community by disclosing social responsibility (JSR) and institutional governance (ICG) as well as the distribution of Zakat funds (ZPR), but these efforts are still not optimal. The study aimed to analyze the impact of JSR, ICG and ZPR on reputation, represented by Third Party Fund (DPK) of Islamic Comercial Bank in Indonesia (BUS). The population of this study was purely BUS in Indonesia for the period 2016-2020. Samples were selected by positive sampling method with a total of 7 BUS samples. The analytical method used is panel data regression, with e-views 9.0 analysis tool. The results showed that JSR had a significant effect on reputation, while ICG and ZPR had no significant effect on reputation. It can be concluded that JSR can progress notoriety while ICG and ZPR have not been able to affect reputation, because currently many Islamic banks have not implemented ICG properly while the distribution of zakat (ZPR) has not had an impact on community economic empowerment.